Anticancer drugs targeting the mitochondrial electron transport chain - Rohlena, Jakub; Dong, Lan-Feng; Ralph, Stephen J; Neužil, Jiří (Antioxidants & redox signaling, 2011)
SIGNIFICANCE: Mitochondria are emerging as highly intriguing organelles showing promise but that are yet to be fully exploited as targets for anticancer drugs. RECENT ADVANCES: A group of compounds that induce mitochondrial destabilization, thereby affecting the physiology of cancer cells, has been defined and termed 'mitocans.' Based on their mode of action of targeting in and around mitochondria, we have placed these agents into several groups including hexokinase inhibitors, compounds targeting Bcl-2 family proteins, thiol redox inhibitors, VDAC/ANT targeting drugs, electron transport chain-targeting drugs, lipophilic cations targeting the inner membrane, agents affecting the tricarboxylic acid cycle, drugs targeting mtDNA, and agents targeting other presently unknown sites. CRITICAL ISSUES: Mitocans have a potential to prove highly efficient in suppressing various malignant diseases in a selective manner. They include compounds that are currently in clinical trial and offer substantial promise to become clinically applied drugs. Here we update and redefine the individual classes of mitocans, providing examples of the various members of these groups with a particular focus on agents targeting the electron transport chain, and indicate their potential application in clinical practice. FUTURE DIRECTIONS: Even though reactive oxygen species induction is important for the anticancer activity of many mitocans, the precise sequence of events preceding and following this pivotal event are not yet fully clarified, and warrant further investigation. This is imperative for effective deployment of these compounds in the clinic.
Keywords: Neoplasms; Electron Transport Chain Complex Proteins; nádory; Animals; mitochondrie; elektronový transportní řetězec; cílená molekulární terapie; lidé; zvířata; Antineoplastic Agents; protinádorové látky; Molecular Targeted Therapy; Mitochondria; Electron Transport; transport elektronů; Humans